Deciphering Drug Targets for Alzheimer's Disease - Kumar, Dileep; Patil, Vaishali M.; Wu, Dee.; Thorat, Nanasaheb (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book explains the fundamental characteristics and biofunctionality of Alzheimer's Disease drug targets and provides up-to-date information on the full range of their biomedical applications. An introductory section gives an overview of the recent developments related to drug targets identified and studied related to Alzheimer's Disease and key developments from preclinical and clinical studies focusing on various molecular targets related to AD and dementia by subject experts all around the globe. Here, individual chapters address the progress and perspectives in human and non-human research, role of various biomarkers as an overview, advanced gene therapy, and novel compounds for therapeutic targets for Alzheimer's disease. The book will be essential reading for graduate students, scientists, and engineers in any of the biomedical research fields in which efforts are being made to utilize novel drug targets and develop effective strategies for new drug targeting and delivery in Alzheimer's disease treatment.
Chapter 1.Deciphering New Drug Targets in Alzheimer's Disease -- Chapter 2. Novel Therapeutic Targets for Treating Alzheimer's Disease -- Chapter 3. Modified Investigation Tools and Techniques Useful in Alzheimer's Disease Research -- Chapter 4. Dual Specificity Tyrosine Phosphorylation Regulated Kinase1A (DYRK1A) Inhibitors: The Quest for a Disease-Modifying Treatment for Alzheimer's Disease -- Chapter 5. -secretase as a primary drug target of Alzheimer disease: Function, Structure, and Inhibition -- Chapter 6. Endocrine Receptors: The Potential Therapeutic Targets for Alzheimer's -- Chapter 7. Calcium Channels as a Potential Therapeutic Target for Alzheimer's Disease -- Chapter 8. Traversing Through the Trajectory of Pathogenic Astrocytes in Alzheimer's Disease -- Chapter 9. Targeting Mitochondrial Dynamics as a Restorative Approach in the Treatment of Alzheimer's Disease -- Chapter 10. Epigenetic Therapy for Alzheimer's Disease -- Chapter 11. Exploring the Diverse Roles of GSK-3ß Kinase in Alzheimer's Disease -- Chapter 12. Role of Target Fishing in Discovery of Novel Anti-Alzheimer's Agents: In Silico Applications -- Chapter 13. Multi-Target Directed Ligand Approach in Anti-Alzheimer's Drug Discovery -- Chapter 14. Investigating the Role of Tau Proteins in Alzheimer's Disease-From Typical Functioning MAPs to Aberrant Fibrillary Deposits in the Brain -- Chapter 15. The Overview of Drugs Used in Alzheimer's Disease and Their Molecular Targets.
Keywords: Medicine -- Research; Biology -- Research; Biology; Neurosciences; Biotechnology; Drug delivery systems; Biomedical Research; Biological Sciences; Neuroscience; Biotechnology; Drug Delivery